Effect of bismuth additions on wettability, intermetallic compound, and microhardness properties of Sn-0.7Cu on different surface finish substrates - Mohd Izrul Izwan Ramli; Mohd Arif Anuar Mohd Salleh; Siti Farahnabilah Muhd Amli; Nurul Razliana Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2020)
The influence of bismuth (Bi) addition on wettability, thickness of interfacial intermetallic compound (IMC), and microhardness properties of Sn-0.7Cu + xBi solder alloy using different types of substrate were examined. The 0.5, 1.0, 1.5, and 2.0 wt. % Bi was added into Sn-0.7Cu and fabricated using the casting process. The result shows that the influence of 1.5 wt. % Bi in the Sn-0.7Cu solder soldered on copper organic solderability preservative (Cu-OSP) and immersion tin (Im-Sn) surface finish has improved the wettability and microhardness. Subsequently, the IMC thickness of Sn-0.7Cu+1.5Bi solder alloy on Im-Sn surface finish gives a better result than reflowed on Cu-OSP. Generally, with the addition of 1.5 wt. % Bi in Sn-0.7Cu solder alloy reflowed on the Im-Sn surface finish had enhanced the performance in terms of wettability, thickness of IMC and microhardness properties compared to on Cu-OSP surface finish.